Allelopathic Assesments of Ficus deltoidea Varieties and Ficus microcarpa - Nornasuha, Yusoff; Nashriyah, Mat; Jumiati, Asis (2018)
This study described allelopathic potential of two medicinal plant species; Ficus deltoidea varieties in comparison with Ficus microcarpa, by testing the leaf-litter through sandwich method and the leaf extracts through methanolic extraction method. These studies were carried out with three replications in Complete Randomized Design (CRD). The sandwich method was carried out by using 5 mg, 10 mg and 50 mg dry weight of the donor plants leaf. Among the eight donor plant tested, results showed that F. deltoidea var. kunstleri had the highest growth inhibition on lettuce radicle elongation (57.51%) as compared to control, followed by F. deltoidea var. trengganuensis (45.50%) and Ficus microcarpa (39.95%), respectively. Meanwhile, the methanolic extraction was done by using different concentrations of leaf extract (0.1 mg/mL , 1 mg/mL, 10 mg/mL and 100 mg/mL). Ficus deltoidea var. kunstleri and var. trengganuensis that have the highest inhibition on lettuce growth in Sandwich method, were further selected to be tested by using methanolic bioassay method. Ficus deltoidea var. kunstleri and F. deltoidea var. trengganuensis were observed to have high inhibition on lettuce radicle elongation at 66.63% and 64.95%, respectively, at concentration 100 mg/mL.